Effects of yttrium doping on structural, electrical and optical properties of barium titanate ceramics. Issue 9 (September 2022) - Islam, Suravi; Khatun, Nazia; Habib, Md. Shehan; Uddin Farhad, Syed Farid; Tanvir, Nazmul Islam; Ali Shaikh, Md. Aftab; Tabassum, Samia; Islam, Dipa; Hossain, Md. Sajjad; Siddika, Ayesha
Abstract: In this report, we study the Yttrium-doped Barium Titanate (Y-BT) Ba1 − x Yx TiO3 (with x = 0.00, 0.01, 0.03, 0.05, 0.07 mmol) perovskite ceramics synthesized by sol-gel method. The as-made powder samples were pressed into a pellet shape and subsequently sintered at 1300 °C for 5 h in air. The structural, morphological, electrical, and optical properties of the synthesized samples were investigated by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), impedance analyzer, and UV-Vis-NIR Spectroscopy respectively. The XRD study revealed the formations of single phase tetragonal structure of Barium Titanate (BT) with ∼23–33 nm mean crystallite size. The crystallite size increases initially with Y-doping, found at about 33 nm for x = 0.01, and reduces for increase in Y 3+ concentration further. The microstructural study from FESEM depicts the uniform distribution of compact and well-faceted grain growth for Y-BT in contrast with undoped barium titanate. The average grain size (∼0.29–0.78 μm) of the Y-BT decreases with increasing doping concentration. Frequency-dependent impedance analyses show enhanced dielectric properties like dielectric constant, quality factor, and conductivity with low dielectric loss in the presence of Yttrium. The optical bandgap energy (∼2.63–3.72 eV) estimated from UV-Vis-NIR diffuse reflection data shows an increasing trend with a higher concentration of yttrium doping. Abstract : Barium titanate; X-ray diffraction; Dielectric properties; Scanning electron microscopy; Optical properties.